2022
DOI: 10.3390/ijms231911453
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Clinical Trials on Neurological Disorders: Trends in Stem Cells Origins, Indications, and Status of the Clinical Trials

Abstract: Neurological diseases can significantly reduce the quality and duration of life. Stem cells provide a promising solution, not only due to their regenerative features but also for a variety of other functions, including reducing inflammation and promoting angiogenesis. Although only hematopoietic cells have been approved by the FDA so far, the number of trials continues to expand. We analyzed 492 clinical trials and illustrate the trends in stem cells origins, indications, and phase and status of the clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This breakthrough has allowed for the study and treatment of genetic diseases, particularly neurological disorders [ 14 ]. Clinical trials of the application of stem cells as a therapeutic approach to tackle various neurological disorders, encompassing conditions such as injuries affecting the brain, spinal cord and peripheral nerves, are now being performed [ 15 ]. Also, stem cell-derived motor neurons have aided in the discovery of amyotrophic lateral sclerosis drugs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This breakthrough has allowed for the study and treatment of genetic diseases, particularly neurological disorders [ 14 ]. Clinical trials of the application of stem cells as a therapeutic approach to tackle various neurological disorders, encompassing conditions such as injuries affecting the brain, spinal cord and peripheral nerves, are now being performed [ 15 ]. Also, stem cell-derived motor neurons have aided in the discovery of amyotrophic lateral sclerosis drugs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that MSCs could be isolated from adipose tissue [ 14 , 17 ]. It has been shown that adipose MSCs (AMSCs) with multipotentiality give rise to adipocytes, neurocytes, chondrocytes, myocytes, and osteoblasts cell lineages [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regenerative potential of mesenchymal stem cells of different origins has been studied and contrasted by numerous research groups (40)(41)(42). The source from which organ-specific mesenchymal stem cells have traditionally been extracted is bone marrow.…”
Section: Introductionmentioning
confidence: 99%